Práticas inclusivas e representações sociais do aluno com deficiência intelectual (D.I.) - Mendes, Cristianne Beda de Queiroz (2016)
Noticing the complexity of inclusion of deficient students at usual school class in addiction the difficulties which are dealing by the teachers during the process of their work it is asked: in what degree are the teachers getting to attend the school demands of the deficient students, in special those ones who are identify with Intellectual Deficiency (ID) and which are the pedagogical practices implemented in this process? And still more are these practices those come from the contact and acting with students with intellectual deficiency innovated or are practices that had been reiterated in the normal process with those worked with the students with the learning difficulties( LD) which ones have already instituted in the docent working? The current working has as purpose to try going through the direction of the inclusion of the students with intellectual deficiency through the studies of the pedagogical including practices and the social representations of the students with intellectual deficiency. For doing this the study was divided into two phases. In the first phase which was called exploratory working which five teachers were interviewed with experience in the working with students with ID and whose the purpose of it was to identify their perception about the pedagogical characteristics and practices. These data were used to structure the following questionnaire used in the next step. In the second phase was actualized two studies through the application of two questionnaires with volunteer teachers. The first study with social representations of the students with ID and pedagogical including practices had the participation of 38 teachers. The second one with the students with the social representations of the students with ID had the participation of 40 teachers. The findings show that the social representations of the student with ID are still been developed and they are formed the base that the student with ID is an absent-minded, excited one showing several kinds of difficulties as school ones( writing, reading and understanding) and as social ones. The teachers try to supply these difficulties with guide practices by educational guidelines, as the conducting of these students to the recourse room with the purpose to have a specialized attendance. Emphasize the importance given by the teacher to the professional appraisal and the importance of the docent education in the structure of the social representations in the educational context.